Total Factor Productivity Analysis of Oil Palm Production in Indonesia - Nuryartono, Nunung; Pasaribu, Syamsul Hidayat; Panggabean, Pristi Nadhilah Khairina (International Journal of Economics and Financial Issues, 2016)
Over the last few decades, Indonesian oil palm industry has grown significantly becoming a very important agriculture-based industry, where the country is today the first world's leading producer and exporter. Total Factor Productivity (TFP) is a framework that can be employed to analyze the source of economic growth. Using the data from the National Farmers Panel Data Survey (PATANAS) for the year 2009 and 2012 in two observed districts respectively in Sanggau and Muaro Jambi disctrict, the results of determinant factors analysis shows that Land, Pesticide, Fertilizer and Labor have significant contribution to total production of oil palm in both districts. On the other hand, based on accounting approach, the result reveals that TFP index values of the districts of Sanggau and Muaro Jambi respectively were 1.56 and 1.03. This study have important implications on how to facilitate the adjustment of small farmers to more efficient oil palm production. Keywords: Oil Palm, Total Factor Productivity, Indonesia JEL Classifications: D24; O3; O33; Q12